A new cryptic species of Pseudopestalotiopsis from Taiwan - Ariyawansa, Hiran A.; Tsai, Ichen; Gareth Jones, E. B. (Phytotaxa, 2018)
The genus Pseudopestalotiopsis comprises 14 formerly illustrated species and are well-known for their capability to produce unique medicinal compounds that may have pharmaceutical and agricultural applications. We elucidate a taxon of Pseudopestalotiopsis that is new to science collected from Diospyros sp. in Nantou County, Taiwan. We conducted polyphasic studies using single- and concatenated-gene (ITS, TEF1, TUB) phylogenies coupled with morphology to evaluate the taxonomic position of the novel taxon. The results indicate that our Pseudopestalotiopsis isolate is morphologically and phylogenetically distinct from its closely related species Ps. camelliae-sinensis and should be acknowledged here as a Ps. hydeae sp. nov. Further, this study increases the base of information regarding the diversity of Pseudopestalotiopsis species that occur in Taiwan.